Analysis of abnormal ALT in blood donors in five Zang autonomous prefectures of Qinghai Province, China: characteristics and screening strategies - DANG Yingnan; Shana Halemubieke; TANG Rong; HUANG Liqin; WU Hailin; CHEN Tingting; LI Shengju; SUN Yanli; ZHENG Xin; LI Yanxia; YE Xianlin; ZENG Jinfeng (Zhongguo shuxue zazhi)
[Objective] To investigate the factors associated with alanine aminotransferase (ALT) abnormalities in multi-ethnic blood donors across five Zang autonomous prefectures in the plateau regions of Qinghai Province, and to provide evidence for ensuring blood safety and formulating screening strategies. [Methods] A retrospective analysis was performed on the ALT abnormal test results of blood donors in the Zang autonomous prefectures of Qinghai from 2022 to 2024. The correlations between ALT levels and factors including gender, age, altitude, and infectious markers were investigated. [Results] The overall ALT unqualified rate among blood donors in this region was 9.01%. Significant differences in ALT levels were observed across genders and age groups (P<0.05). Variations in ALT abnormality rates were also noted among different plateau regions (P<0.05). Overall, ALT values exhibited an increasing trend with rising altitude. The average ALT unqualified rates were 11.19% in Zang donors, 7.96% in Han donors, and 4.79% in donors from other ethnic groups (P<0.05). No statistically significant association was observed between ALT abnormality and the presence of HBV/HCV infectious markers (P>0.05). [Conclusion] In the plateau areas of Qinghai, multi-ethnic blood donors have a relatively high ALT levels and ALT unqualified rates, showing distinct regional characteristics. ALT elevation in voluntary blood donors is related to non-pathological factors such as gender, age, and dietary habits, but not to infectious indicators.